2006
DOI: 10.1111/j.1468-5965.2006.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Media Effects on Public Opinion about the Enlargement of the European Union*

Abstract: Studies of public support for matters of European integration tend either to neglect or inadequately model the role of the mass media. This study investigates how news media content affects public support for the enlargement of the EU. Other influences on support for integration, such as economic evaluations, anti-immigration sentiment, domestic political considerations and cognitive mobilization are accounted for. The study draws on two-wave panel surveys and media content analyses of television news and nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 37 publications
6
86
0
2
Order By: Relevance
“…Our findings offer support for the literature on media effects on attitudes towards EU enlargement (De Vreese and Boomgaarden, 2006;Schuck and De Vreese, 2006). The data analysis shows that exposure to the mass media has an impact on support for Macedonia's accession to the EU (see Table 1).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings offer support for the literature on media effects on attitudes towards EU enlargement (De Vreese and Boomgaarden, 2006;Schuck and De Vreese, 2006). The data analysis shows that exposure to the mass media has an impact on support for Macedonia's accession to the EU (see Table 1).…”
Section: Resultssupporting
confidence: 87%
“…This finding strongly supports the studies carried out by De Vreese and Boomgaarden (2006) and Schuck and De Vreese (2006). In the case of our culture variable, the decline in support is statistically significant.…”
Section: Resultssupporting
confidence: 82%
“…Hobolt (2006) and Garry et al (2005) showed that party endorsement indeed mattered for the results in the Danish referendum on the Maastricht Treaty: if the party they supported advocated a 'yes' vote, the likelihood of people voting 'yes' in the referendum increased, regardless of their attitudes. Franklin et al (1994) and De Vreese and Boomgaarden (2006) point to the importance of domestic political evaluations. Because the national government is the institution involved in the treaty negotiations on the European constitution, trust in national politics will inevitably be part of the voting behaviour.…”
Section: Political Approachmentioning
confidence: 99%
“…This pattern of news coverage has been found to apply to EU summits, which are pivotal moments for EU decision-making and where news coverage of EU affairs is much more visible than during 'routine periods' (De Vreese and Boomgaarden, 2006;Peter and de Vreese, 2004;Semetko and Valkenburg, 2000). During other key events, such as national referendums on issues of European integration, EU news can take up a substantial part of the news agenda, especially in the final weeks of the campaign (De Vreese and Semetko, 2004).…”
Section: How Visible Is the Eu On The News Agenda?mentioning
confidence: 99%